DIFFERENCES IN ACCULTURATION ORIENTATIONS OF ADVANTAGED AND DISADVANTAGED MEMBERS OF THE HOST COMMUNITY IN TÜRKIYE TOWARD NEWCOMERS: THE ROLES OF ETHNIC AND NATIONAL IDENTIFICATION AND PERCEIVED OUTGROUP THREAT - Sayılan, Gülden; Çoksan, Sami; Can, Mine (University of Salento, 2024)
This study examines the links between ethnic identification, perceived threat, and acculturation expectations of the host members in samples of Turks and Kurds. Using a cross-sectional correlational method, we test whether (1)the members of the advantaged and disadvantaged groups differ in terms of their acculturation orientations; (2)the ingroup identification becomes salient when host members evaluate their relationship with the newcomer differs between them, and (3)members of the advantaged and disadvantaged groups differ in terms of the relationship ethnic and national identification have with the perceived threat from Syrian refugees and their acculturation orientations. Results (N=579) from a series of simple mediation models indicated that perceived outgroup threat mediates the link between ethnic identification and acculturation expectations among Turks for the models including assimilation, segregation, exclusion, and individualism-based acculturation expectation as the outcomes. We found no mediating role of the perceived outgroup threat for Kurds. The mixed-model MANCOVA results show that Kurds had more integration-based expectations than the Turks. Turks had more assimilation and exclusion-based acculturation expectations than Kurds. We discussed the results in the context of the social identity approach. © 2024, University of Salento. All rights reserved.
Keywords: acculturation expectancies; ethnic identification; national identification; perceived outgroup threat; refugees